Review on fixed-frequency beam steering for leaky wave antenna - J. S. Kasim; M. S. M. Isa; Z. Zakaria; M. I. Hussein; Mowafak K. Mohsen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper aims to survey the efforts of researchers in response to the novel and effective technology of control radiation pattern at a fixed frequency for leaky wave antenna (LWA), map the research landscape from the literature onto coherent taxonomy and determine the basic properties of this potential field. In addition, this paper investigates the motivation behind using beam steering in LWA and the open challenges that impede the utility of this antenna design. This paper offers valuable recommendations to improve beam steering in LWA. The review revealed the development and improvement of several techniques of beam scanning LWA. However, several areas or aspects require further attention. All the articles, regardless of their research focus, attempt to address the challenges that impede the full utility of beam scanning and offer recommendations to mitigate their drawbacks. This paper contributes to this area of research by providing a detailed review of the available options and problems to allow other researchers and participants to further develop beam scanning. The new directions for this research are also described.